Польська аграрна реформа та її реалізація у 20-х рр. ХХ ст. на західноукраїнських землях - Виздрик, В. С. (Видавництво Львівської політехніки, 2013)
Розглянуто питання впровадження урядової аграрної реформи у Західній Україні у міжвоєнний період шляхом парцеляції, що сприяла виникненню господарств фермерського типу, насамперед господарств польських осадників. Реалізація аграрної реформи не зупинила процесу здрібнення селянських землеволодінь, а також вкрай загострила соціальні та національні суперечності між українським й польським населенням краю. The article overviews the implementation of the governmental agrarian reform in Western Ukraine in the interwar period conducted by parcelling, which contributed to the appearence of farming households, especially households of the Polish colonists. The implementation of the agrarian reform did not stop the process of rural land assets’ diminishing and the extremely aggravated social and national contradictions between the Ukrainian and the Polish population of the province.